Divergent dynamics of inflammatory mediators and multiplex PCRs during airway infection in cystic fibrosis patients and healthy controls: Serial upper airway sampling by nasal lavage - Erdmann, Nina; Schilling, Theresa; Hentschel, Julia; Lehmann, Thomas; von Bismarck, Philipp; Ankermann, Tobias; Duckstein, Franziska; Baier, Michael; Zagoya, Carlos; Mainz, Jochen G. (Frontiers in Immunology, 2022)
Background: In cystic fibrosis (CF), acute respiratory exacerbations critically enhance pulmonary destruction. Since these mainly occur outside regular appointments, they remain unexplored. We previously elaborated a protocol for home-based upper airway (UAW) sampling obtaining nasal-lavage fluid (NLF), which, in contrast to sputum, does not require immediate processing. The aim of this study was to compare UAW inflammation during stable phases and exacerbations in CF patients and healthy controls. Methods: Initially, we obtained NLF by rinsing 10ml of isotonic saline/nostril during stable phases. During exacerbations, subjects regularly collected NLF at home. CF-patients directly submitted one aliquot for microbiological cultures, the remaining were immediately frozen until transfer on ice to our clinic. Interleukins (IL)-1β/-6/-8, neutrophil elastase (NE), matrix metalloproteinase (MMP)-9 and tissue inhibitor of metalloproteinase (TIMP)-1 were assessed. Results: Altogether, 49 CF patients and 38 healthy controls completed the study and 214 NLF samples were analyzed. 20/49 CF patients were at least intermittently colonized with P.aeruginosa and received azithromycin and/or inhaled antibiotics as standard therapy. At baseline, IL-6 and IL-8 tended to be elevated in CF, compared to controls. During infection, inflammatory mediators increased in both cohorts, reaching significance only for IL-6 in controls (p=0.047). Inflammatory responses tended to be higher in controls (1.6-fold (NE) to 4.4-fold (MMP-9)), while in CF, mediators increased only moderately (1.2-1.5-fold (IL-6/IL-8/NE/TIMP-1/MMP-9)). Patients receiving inhalative antibiotics or azithromycin (n=20 and n=15, respectively) revealed lower levels of IL-1β/-6/-8, and NE during exacerbation, compared to CF patients not receiving those antibiotics. In addition, CF patients receiving azithromycin showed MMP-9 levels significantly lower than CF patients not receiving azithromycin at stable phase and exacerbation. Conclusion: Non-invasive and partially home-based UAW sampling opens new windows for assessment of inflammation in the unified airway system.